Kedisiplinan Kerja dan Komitmen Organisasi sebagai Fondasi Kinerja Aparatur Sipil Negara di Pelayanan Terpadu Satu Pintu Lembaga Pemasyarakatan Narkotika Kelas IIA Yogyakarta - Anastasia Fitri Ariyantini; Dwi Utami Puterisari (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze the influence of work discipline and organizational commitment as the foundation of the performance of the State Civil Apparatus (ASN) at the One-Stop Integrated Service (PTSP) of the Yogyakarta Class IIA Narcotics Correctional Institution. The research method used a descriptive quantitative approach with data collection through a Likert scale questionnaire. The results show that the work discipline variable obtained a mean value of 3.68 in the excellent category, which describes punctuality, attendance, compliance with rules, and high responsibility. The organizational commitment variable also obtained a mean value of 3.68 in the excellent category, reflecting strong affective, continuance, and normative commitment. These findings confirm that work discipline and organizational commitment have a synergistic relationship in shaping effective and public service-oriented ASN performance. Improvements in discipline and commitment can be achieved through continuous coaching, leadership role modeling, and a fair reward system. The overall results confirm that discipline and organizational commitment are the main pillars in building ideal services.